2011
DOI: 10.4061/2011/276308
|View full text |Cite
|
Sign up to set email alerts
|

The Value of PIC Cystography in Detecting De Novo and Residual Vesicoureteral Reflux after Dextranomer/Hyaluronic Acid Copolymer Injection

Abstract: The endoscopic injection of Dx/HA in the management of vesicoureteral reflux (VUR) has become an accepted alternative to open surgery. In the current study we evaluated the value of cystography to detect de novo contralateral VUR in unilateral cases of VUR at the time of Dx/HA injection and correlated the findings of immediate post-Dx/HA injection cystography during the same anesthesia to 2-month postoperative VCUG to evaluate its ability to predict successful surgical outcomes. The current study aimed to eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
2
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 14 publications
1
2
0
Order By: Relevance
“…This was confirmed by a 2011 study, which demonstrated an 80% positive correlation between intraoperative negative PIC cystography and postoperative positive VCUG after endoscopic injection of Dx/HA [18].…”
Section: Discussionsupporting
confidence: 72%
“…This was confirmed by a 2011 study, which demonstrated an 80% positive correlation between intraoperative negative PIC cystography and postoperative positive VCUG after endoscopic injection of Dx/HA [18].…”
Section: Discussionsupporting
confidence: 72%
“…Palmer et al [9] reported that 27 of the 34 patients, who were preoperatively diagnosed with unilateral VUR, intraoperatively demonstrated a positive PIC cystography in the contralateral ureters. The PIC-VUR correction was endoscopically performed without any complications and new postoperative contralateral VUR.…”
Section: Discussionmentioning
confidence: 98%
“…ing new contralateral VUR in cases of preoperatively unilateral VUR [7]. The major advantages of PIC cystography are the detection of occult VUR that cannot be detected by standard VCUG and the performance of simultaneous injection therapy to prevent VUR under the same anesthesia.…”
mentioning
confidence: 99%